Detection of neuropeptide Y and its mRNA in megakaryocytes: enhanced levels in certain autoimmune mice. - Ericsson, A (1987)
Neuropeptide tyrosine (neuropeptide Y, NPY) is a potent vasoconstrictor with a wide distribution in the central and peripheral nervous systems. Here we show that high levels of rat NPY mRNA are also found in peripheral blood cells, bone marrow, lung, and spleen. Furthermore, radioimmunoassay revealed high levels of NPY-like peptide in these tissues. In mice, the levels of splenic NPY mRNA and immunoreactive peptide differed extensively between strains and were greatly elevated in several strains (NZB, NZBxW, and BXSB) that develop a disease resembling human systemic lupus erythematosus. Like the rat, the NZB mouse showed a high content of NPY mRNA in peripheral blood cells and bone marrow. Immunohistochemical staining revealed NPY-like immunoreactivity in large cells morphologically identifiable as megakaryocytes in rat bone marrow and in the spleen of the NZB mouse strain. Expression of NPY mRNA in megakaryocytes in rat bone marrow and NZB mouse spleen was confirmed by in situ hybridization. These results indicate that NPY is synthesized in megakaryocytes, implying that NPY can be released from platelets and function as a vasoconstrictor during blood-vessel damage. In addition, the increase in splenic NPY in certain autoimmune mouse strains adds to the list of abnormalities associated with these strains.